ANALISIS KONTRASTIF AFIKSASI VERBA BAHASA INDONESIA DAN BAHASA INGGRIS PADA KARTUN BERBIE - Jannah, Maftuhatul; Ade Kartika Devi (PT. CASA CENDEKIA MEDIA, 2024)
This research analyzes cross-language contrasts in the form of verb affixations in Indonesian and English. The data sources used in this research are the Berbie cartoon entitled